2013
DOI: 10.1007/s10151-013-1017-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between prucalopride efficacy and constipation type

Abstract: Patients with all categories of constipation may respond to prucalopride. A trial regime may be indicated regardless of the aetiology of the constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…Tegaserod, a partial agonist at the 5-HT4 receptor, marketed for short term treatment of IBS, was withdrawn recently due to cardiovascular complications. Another related compound prucalopride recently demonstrated superior efficacy and generally minor side effects, headache being the most common [40]. However, in a recent clinical trial the efficacy of prucalopride was not statistically significantly different relative to a placebo [41].…”
Section: Management Of Ibsmentioning
confidence: 99%
“…Tegaserod, a partial agonist at the 5-HT4 receptor, marketed for short term treatment of IBS, was withdrawn recently due to cardiovascular complications. Another related compound prucalopride recently demonstrated superior efficacy and generally minor side effects, headache being the most common [40]. However, in a recent clinical trial the efficacy of prucalopride was not statistically significantly different relative to a placebo [41].…”
Section: Management Of Ibsmentioning
confidence: 99%
“…Prucalopride is a 5-HT 4 receptor agonist that accelerates colonic transit and improves constipation symptoms [16]. A recent meta-analysis that included 11 randomized controlled trials showed significant improvement in the number of CSBMs in response to treatment with prucalopride.…”
Section: Prucalopridementioning
confidence: 99%
“…Prucalopride is a selective 5-HT 4 receptor agonist with prokinetic activity that is known to accelerate colonic transit and improve constipation related complaints. 68 Prucalopride stimulates high-amplitude propagated contractions and increases segmental contractions, which are likely to be the under-lying mechanisms of its effects on bowel habits. 69 Three trials (which assessed 620, 641 and 713 patients, respectively) examining the use of prucalopride in CC demonstrated a significant increase in the proportion of patients achieving at least 3 SBMs per week compared with placebo.…”
Section: Serotonin Receptor Modulatorsmentioning
confidence: 99%